2015
DOI: 10.1016/j.amsu.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of herbal medicine Dai-kenchu-to on portal blood flow in rat models

Abstract: IntroductionTo clarify the influence of Dai-Kenchu-To (DKT) on portal blood flow (PBF), PBF was continuously measured with Doppler ultrasound.MethodsNormal liver rats were divided into a DKT 90 mg/kg, DKT 270 mg/kg administered group, and control, while cirrhotic liver rats were divided into a DKT-LC 90 mg/kg administered group and Control-LC. The PBF was measured after the administration of either DKT or water for 60 min by laser Doppler flowmetry system.ResultsThe PBF in the DKT 90 increased approximately 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Basically, the active ingredient in TJ-100 most attributable to this effect is dried ginger rhizome [13]. Our previous study demonstrated an increase in the PBF after intragastric administration of TJ-100 in the normal liver rat model [14]. Theoretically, increase of the intestinal blood flow volume should increase the volume of PBF.…”
Section: Control Group N=8mentioning
confidence: 99%
“…Basically, the active ingredient in TJ-100 most attributable to this effect is dried ginger rhizome [13]. Our previous study demonstrated an increase in the PBF after intragastric administration of TJ-100 in the normal liver rat model [14]. Theoretically, increase of the intestinal blood flow volume should increase the volume of PBF.…”
Section: Control Group N=8mentioning
confidence: 99%
“…TJ-100 TSUMURA Daikenchuto Extract Granules consist of a dried extract of a mixture containing processed ginger, ginseng, zanthoxylum fruit, and maltose. It is clinically used to treat postoperative symptoms accompanied by abdominal pain and bloating sensation such as paralytic ileus and bowel move-ment disturbance, and the reported action mechanisms are enhanced gastrointestinal motility [1][2][3], increased intestinal blood flow [4,5] and anti-inflammatory effects [6,7]. Previous studies reported postoperative effects of DKT as shortening of the time to first defecation [8], first gas passage [9], and oral intake recovery [10] after abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%